Pengaruh Islamic Marketing Mix, Service Quality dan Customer Value terhadap Kepuasan Nasabah Bank Syariah Indonesia - Chairunnisa Oktaviani; Ina Sintia; Maya Panorama; Siti Salsabila (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Service provider, especially banks, are faced challenges of financial technology which is growing rapidly. In this case sharia banking is required to be able to pursue conventional banks and technology changes. Bank Syariah Indonesia is obliged to meet every customer's needs in Islamic life with various services. This study aims to determine the effect of Islamic Marketing Mix, Service Quality dan Customer Value on customer satisfaction of Islamic banks in Indonesia. This study uses a quantitative approach using a questionnaire distributed to customers of Bank Syariah Indonesia KC Palembang. The instrument testing in this study used descriptive statistical methods, validity tests, reliability tests, multiple regression tests, F tests, T tests. The results showed that: (1) Islamic marketing mix had no effect on customer satisfaction of Bank Syariah Indonesia, (2) Service Quality has an effect on customer satisfaction of Bank Syariah Indonesia, (3) Customer Value has an effect on customer satisfaction of Bank Syariah Indonesia. The magnitude of the influence of service quality and customer value indicates that there is a significant influence on customer satisfaction of Bank Syariah Indonesia. Keywords: Customer Value, Customer Satisfaction, Islamic Marketing Mix, Service Quality